Mekanisme Pembuatan Loading Dokumen MT. Lucky Star 06 pada Tersus Ivo Mas Tunggal oleh PT. Tarunacipta Kencana Dumai Branch - Maya Mawaddah Boangmanalu; Suratni Ginting (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines the mechanism of preparing loading documents for MT. Lucky Star 06 at the Ivo Mas Tunggal Private Terminal, managed by PT. Tarunacipta Kencana Dumai Branch. Loading documents are official records prepared during the liquid cargo loading process on a tanker to ensure operational smoothness, regulatory compliance, and administrative as well as legal requirements. The research methods employed were field research through direct observation during shore practice and library research to strengthen the theoretical foundation. The preparation mechanism begins with the shipping instruction (SI) from the shipper and voyage information from the shipowner, which are compiled into the bill of lading. Once received from the head office in Jakarta via email, the agent prepares a draft version to anticipate potential data changes during the loading process. Supporting documents include the shipping instruction, bill of lading, and MARPOL for pollution identification. The loading documents consist of three main components. The first is the cargo manifest, containing a complete cargo list, including vessel details, ports of loading/discharge, consignor, consignee, and cargo descriptions. The second is the mate’s receipt, serving as evidence of cargo acceptance by the vessel. The third is the statement of fact, which records all vessel activities from clearance in to clearance out based on the time sheet. Challenges identified include internet connection disruptions that hinder data input from surveyors or shippers, and errors caused by insufficient accuracy in data entry, particularly punctuation. Solutions applied involve continuous monitoring of operational emails and thorough rechecking of documents before submission to the vessel to ensure accuracy and completeness.